HISTOPATHOLOGY GILLS AND KIDNEYS OF SIAMESE JAMBAL FISH (Pangasius hypophthalmus) INFECTED WITH BACTERIA Aeromonas hydrophila AND TREATED WITH Rhizophora sp. LEAF EXTRACT - Fitria Sufriyani; Henni Syawal; Morina Riauwaty S (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractMAS disease(Motile Aeromonas Septicemia)is a serious disease, can attack all types of freshwater fish in tropical areas and can cause 100% death within three days. Treatment with antibiotik and chemicals is not recommended, therefore it is necessary to alternative from natural ingredients such as Rhizophora sp. leaves that have antimakrobial content such as tannins, alkaloids, flavonoids and saponins. The purpose of the research is to find out the effectiveness of Rhizophora sp. leaf extract to treat gills and kidneys of fish infected with Aeromonas hydrophila bacteria. The method is a survey method with a comparatively descriptive data analysis between treatments. Test fish used are siamese jambal fish(Pangasius hypophthalmus) infected with A. hydrophila measuring 13-15 cm. The dosage used for treatment is 0 ppm, 1300 ppm, 1600 ppm, 1900 ppm. Treatment is done by immersion in Rhizophorasp.leaf extract solution for 5 minutes as much as twice with an interval of 24 hours. The parameters measured include; clinical symptoms, gill and renal histopathology, and water quality. Fish organs in the process of histology and coloring (HE). The results showed that Rhizophorasp.leaf extract pointed tochanges in gill tissue and kidneys of fish infected with A. hydrophila. The best dose is 1600 ppm with gill tissue abnormalities in the form of: lamella fusion, while the kidneys show abnormalities in the form of: hypertropy and necrosis.Keywords: Rhizophora sp., Aeromonas hydrophila, Histopathology,Pangasius hypophthalmus